Luminescence and formation of alkalihalide ionic excimers in solid Ne and Ar: Spectroscopy in Cryocrystals and Matrices - Śliwiński, G.; Frankowski, M.; Schwentner, N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Transitions from ionic states A2+X– of alkalihalides CsF, CsCl and RbF isolated in solid Ne and Ar films recorded under pulsed e-beam excitation are studied. The B(2∑1/2)-X(2∑1/2) and C(2П3/2)-A(2П3/2) luminescence bands of Cs2+F– (196.5 nm, 227 nm), Cs2+Cl– (220.1 nm, 249.2 nm) and Rb2+F– (136 nm) in Ne, and a weakerB–X emission of Cs2+F– (211.2 nm) in Ar are identified. For CsF the depopulation of the A2+X– state is dominated by the radiative decay. A ratio of the recorded exciplex emission intensities of I(CsF)/I(CsCl)/I(RbF) = 20/5/1 reflects the luminescence efficiency and for RbF and CsCl a competitive emission channel due to predissociation in the A2+X-(B2∑1/2) state is observed. For these molecules an efficient formation of the state X*2 is confirmed through recording the molecular D`(3П2g)-A`(3П2u) transition. A strong dependence of the luminescence intensities on the alkalihalide content reveals quenching at concentrations higher than 0.7%.